Implementation of E-Government through Moci Legit in Population Administration Services in Sukabumi City 2023-2024 - Simbolon, Sherly Desinta; Sagita, Novie Indrawati (Penerbit Goodwood, 2025)
Purpose: Digital transformation in public services has encouraged local governments to develop e-government, but its implementation still faces various obstacles. Therefore, this study aims to analyze how e-government is implemented in population administration services through the Moci Legit application in Sukabumi City in 2023-2024. Methodology/approach: This research analyzes the application of Moci Legit in population administration services in Sukabumi City in 2023-2024 using qualitative methods. Data collection was conducted through literature studies and field studies consisting of observation, interviews, and documentation. Results/findings: The results showed that the implementation of the Moci Legit application has not been able to fulfill the successful elements of e-government development optimally. In the Support element, socialization has not been carried out thoroughly and consistently. In the Capacity element, there is no special budget for Moci Legit, and the number of human resources available is still insufficient and insufficient. In the Value element, the benefits of Moci Legit can already be felt by the community, but not optimally because there are still various obstacles felt by the community. Conclusions: Disdukcapil Kota Sukabumi needs to set a routine schedule for socialization, allocate special funds for Moci Legit, increase human resources, and conduct periodic evaluations of the Moci Legit application to reduce technical problems that often occur. Limitations: Sukabumi City government's focus on the implementation of e-government in population administration services. Contribution: The research results can provide input and contributions to the Sukabumi City government.